ANALISA FAKTOR-FAKTOR ADOPSI CHATBOT LINE SMB TELKOM DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL YANG DIMODIFIKASI - Singgih Darmawan; Retno Setyorini (ProBank, 2020)
Virtual Assistant Serina SMB Telkom's is the latest technology-based customer service launched by Telkom'sSMB National Admission. The Virtual Assistant who is familiarly called the Serina chatbot can serve questionsas well as complaints of students, new students, and parents through the LINE messenger application. Thisresearch was conducted to determine consumer responses and to see the influence between variables regardingcompatibility, perceived usefulness, perceived ease of use, behavioral intention, and actual use of Serina chatbotusing the TAM approach. This research uses quantitative methods with descriptive and causal research types.The sampling technique uses a non probability sampling technique with a purposive sampling type with a samplesize of 100 respondents. Data analysis techniques using descriptive analysis and SEM-PLS using the outermodel and inner model. Based on the results of descriptive analysis, overall compatibility is in the goodcategory, perceived usefulness in the good enough category, perceived ease of use in the good category,behavioral intention in the good enough category, and actual use in the good enough category. The t-statisticand P-coefficient results show that: compatibility influences perceived usefulness and perceived ease of use,perceived ease of use affects perceived usefulness and behavioral intention, perceived usefulness influencesbehavioral intention and behavioral intention influences actual use.Keywords: Chatbot, Technology Acceptance Model (TAM), Compatibility, Partial Least Square (PLS)